2007
DOI: 10.1007/s00403-007-0774-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of integrins and filaggrin expression by Propionibacterium acnes extracts on keratinocytes

Abstract: Propionibacterium acnes plays an important role in the pathogenesis of acne and it is established that this bacteria is involved in the induction and maintenance of the inflammatory phase of acne. The aim of our work was to determine if P. acnes extracts could modulate integrins and filaggrin in vitro expression by keratinocytes. Integrins and filaggrin expression was examined using immunohistochemistry technique both on Normal Human Epiderminal Keratinocytes (NHEK) and on deep-frozen sections of normal human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 17 publications
4
50
2
5
Order By: Relevance
“…Thus, as CRH modifies the differentiation of keratinocytes, we confirm that this bacterium has a spectrum of action, not limited to inflammation but also in the early stages of the formation of acne lesions. 29 This confirms the fundamental role played by this bacterium which can be detected as a local expression in the epidermis induced by the microbial stressor P. acnes.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Thus, as CRH modifies the differentiation of keratinocytes, we confirm that this bacterium has a spectrum of action, not limited to inflammation but also in the early stages of the formation of acne lesions. 29 This confirms the fundamental role played by this bacterium which can be detected as a local expression in the epidermis induced by the microbial stressor P. acnes.…”
Section: Introductionsupporting
confidence: 67%
“…26,27 Moreover the genome sequence of P. acnes is known to encode many factors that may have inflammatory potential. 28 But, recently it has also been shown that P. acnes was able to induce keratinocytes proliferation and filaggrin expression by keratinocytes, 29 indicating that this bacterium could play a role not only in the development of inflammation in acne lesions but also in the formation of the comedo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yine P. acnes'in mikrokomedonlarda yüksek konsantrasyonda bulunduğu saptanmıştır 7 . Keratinosit proliferasyonunda önemli rolü olan integrinlerden β1, α3, α6s ve ανβ6 integrinlerin de P. acnes ekstreleri tarafından indüklendiği bulunmuştur 8 . Akne patogenezi ile ilgili elde edilen bu bilgiler ışığında P. acnes'in inflamatuvar lezyon oluşumu kadar mikrokomedon oluşum evresinde de önemli role sahip olduğu anlaşılmaktadır.…”
Section: Gi Riflunclassified
“…Филаггрин -это ключе-вой белок, участвующий в эпидермальной диффе-ренцировке, способствующий структурной и функ-циональной целостности рогового слоя эпидерми-са. Выявлено, что P. acnes увеличивают экспрессию филаггрина в культивируемых кератиноцитах, а также в эксплантатах кожи человека [16], т.е. при акне увеличивается экспрессия филаггрина в кера-тиноцитах, выстилающих стенку фолликула [17], но пока неясно, являются ли изменения экспрессии филаггрина при акне первичными или вторичными [18].…”
unclassified